2016
DOI: 10.3847/0004-637x/832/2/117
|View full text |Cite
|
Sign up to set email alerts
|

DECIPHERING CONTRIBUTIONS TO THE EXTRAGALACTIC GAMMA-RAY BACKGROUND FROM 2 GeV TO 2 TeV

Abstract: Astrophysical sources outside the Milky Way, such as active galactic nuclei and star-forming galaxies, leave their imprint on the gamma-ray sky as nearly isotropic emission referred to as the extragalactic gamma-ray background (EGB). While the brightest of these sources may be individually resolved, their fainter counterparts contribute diffusely. In this work, we use a recently developed analysis method, called the Non-Poissonian Template Fit, on up to 93 months of publicly available data from the Fermi Large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 103 publications
(182 reference statements)
15
115
0
Order By: Relevance
“…It is compatible, with even more room for UHECRs, with the estimates of Lisanti et al (2016) for the PS contributions (∼54% and 68% of the EGB Model A around 2 GeV and above 50 GeV, respectively). Only very strong evolutions are excluded by the current observations.…”
Section: Discussionsupporting
confidence: 69%
“…It is compatible, with even more room for UHECRs, with the estimates of Lisanti et al (2016) for the PS contributions (∼54% and 68% of the EGB Model A around 2 GeV and above 50 GeV, respectively). Only very strong evolutions are excluded by the current observations.…”
Section: Discussionsupporting
confidence: 69%
“…Taking uncertainties into account, the upper bound for the non-blazar fraction of the EGB is 28% (6.6 × 10 −10 ph cm −2 s −1 sr −1 ). Lisanti et al (2016) performed a similar NonPoissonian Template Fit (NPTF) of LAT data in the > 50 GeV energy range and found that point sources account for at least 68 +9 −8 % (±10% systematic uncertainty) of the total EGB intensity. The NPTF method loses sensitivity to sources below the single-photon limit, corresponding to a flux of ∼ 4 × 10 −12 ph cm −2 s −1 in the Lisanti et al (2016) analysis, and therefore represents a lower bound on the point-source contribution, as a realistic source population would include contributions from members of the same population significantly below that flux threshold.…”
mentioning
confidence: 99%
“…Lisanti et al (2016) performed a similar NonPoissonian Template Fit (NPTF) of LAT data in the > 50 GeV energy range and found that point sources account for at least 68 +9 −8 % (±10% systematic uncertainty) of the total EGB intensity. The NPTF method loses sensitivity to sources below the single-photon limit, corresponding to a flux of ∼ 4 × 10 −12 ph cm −2 s −1 in the Lisanti et al (2016) analysis, and therefore represents a lower bound on the point-source contribution, as a realistic source population would include contributions from members of the same population significantly below that flux threshold. We note that the contribution of subthreshold sources inferred from the photon fluctuation analysis of Ackermann et al (2016b) is consistent with expectations based on blazar luminosity functions Di Mauro et al 2014b;.…”
mentioning
confidence: 99%
“…Among these we can list anisotropy analyses (Ando & Komatsu 2006Ando 2009;Ackermann et al 2012c;Cuoco et al 2012;Harding & Abazajian 2012;Fornasa et al 2013Fornasa et al , 2016Di Mauro et al 2014b;, pixel statistic analyses (Dodelson et al 2009;Malyshev & Hogg 2011;Feyereisen et al 2015;Lisanti et al 2016;Zechlin et al 2016aZechlin et al , 2016b, and cross-correlations with tracers of the large-scale structure of the universe (Ando 2014;Ando et al 2014;Fornengo & Regis 2014;Shirasaki et al 2014;Camera et al 2015;Cuoco et al 2015;Fornengo et al 2015;Regis et al 2015;Xia et al 2015;Feng et al 2017;Shirasaki et al 2016;Tröster et al 2017), which we will investigate in the following.…”
Section: Introductionmentioning
confidence: 99%